Dialysis in neonates with inborn errors of metabolism. - Schaefer, Franz; Straube, Emine; Oh, Jun; Mehls, Otto; Mayatepek, Ertan (Nephrology, dialysis, transplantation, 1999)
BACKGROUND: Certain inborn errors of metabolism become manifest during the neonatal period by acute accumulation of neurotoxic metabolites leading to coma and death or irreversible neurological damage. Outcome critically depends on the immediate elimination of the accumulated neurotoxins. Recent technological progress provides improved tools to optimize the efficacy of neonatal dialysis. METHODS: We report our experience with continuous venovenous haemodialysis (CVVHD) in six neonates with hyperammonaemic coma due to urea-cycle disorders or propionic acidaemia and in one child with leucine accumulation due to maple-syrup urine disease (MSUD), in comparison with five patients managed by peritoneal dialysis (PD) (2 hyperammonaemia, 3 MSUD). Application of a new extracorporeal device specifically designed for use in small children permitted the establishment of stable blood circuits utilizing small-sized catheters, and the tight control of balanced dialysate flows over wide flow ranges. RESULTS: Plasma ammonia or leucine levels were reduced by 50% within 7.1 +/- 4.1 h by CVVHD and within 17.9 +/- 12.4 h by PD (P<0.05). Also, total dialysis time was shorter with CVVHD (25 +/- 21 h) than with PD (73 +/- 35 h, P<0.02). A comparison of the CVVHD results with published literature confirmed superior metabolite removal compared to PD, and suggested comparable efficacy as achieved with continuous haemofiltration techniques. Apart from accidental pericardial tamponade during catheter insertion in one case, no major complications were noted with CVVHD. In three of the five PD patients, dialysis was compromised by mechanical complications. None of the MSUD patients but four children with urea-cycle disorders died, two during the acute period and two later during the first year of life, with signs of severe mental delay. Of the eight children presenting with hyperammonaemic coma, the four with the most rapid dialytic ammonia removal rate (50% reduction in < 7 h) survived with no or moderate mental retardation, whereas slower toxin removal was always associated with a lethal outcome. Simulation studies showed that the efficacy of neonatal CVVHD is limited mainly by blood-flow restrictions. CONCLUSIONS: While CVVHD is the potentially most efficacious dialytic technique for treating acute metabolic crises in neonates, utmost care must be taken to provide an adequately sized vascular access.
Gesehen am 13.01.2021